KAJIAN POTENSI AGROWISATA DI KAWASAN WISATA COBAN JAHE, DESA PANDANSARI LOR, KECAMATAN JABUNG, KABUPATEN MALANG - Rizki Alfian; Debora Budiyono; Suryadi Umbu Ewang (BUANA SAINS, 2020)
Pandansari Lor Village is one of the tourist villages in the District of Jabung, Malang. Pandansari Lor has the potential for agro-tourism so that tourist visits have increased every year. With the level of agro-tourism activities increasing the volume of visitors is increasing. In addition, the level of understanding of the local community towards agro-tourism is low so it needs to be socialized about agro-tourism. The purpose of this study is to examine the potential of agrotourism in Pandansari Lor village. The research was conducted in November to December 2019, using the inventory method or field survey, and SWOT analysis. Data collection is carried out by means of field observations, calculations, interviews and literature studies. Based on the results of the feasibility assessment of the agro-tourism area, Tegir Hamlet is a hamlet that has the potential to be developed into an agrotourism area because it is ranked first with a total weight of 3.85. Begawan and shadow hamlets have the same number of weights, which is 3.75, which has the potential to be developed as an agro-tourism area while Kedawung Hamlet is the least potential because it is ranked the lowest at 2.85. The main alternative strategies are, optimizing existing agrotourism activities and other supporting agro-tourism objects and attractions, providing training and socialization related to agro-tourism and agriculture through collaboration with many related parties to expand the network on agro-tourism.